ANALISIS KEBIJAKAN PENGEMBANGAN PASAR BULU KOTA SEMARANG BERDASARKAN PERDA NOMOR 9 TAHUN 2013 TENTANG PENGATURAN PASAR TRADISIONAL - Br Peranginangin, Fitri Anggi; Santoso, R. Slamet; Lituhayu, Dyah; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The existence of traditional markets declined with the rapid development of modern markets. The presence of professionally managed modern markets is claimed to have discredited the existence of traditional markets. The development of market revitalization that has been proclaimed by the government is an effort to maintain the existence of traditional market itself, this effort to increase market competitiveness to modern market. This study aims to identify the problem of market development policy of Feathers based on Local Regulation No. 9 of 2013 on Traditional Market Setup and formulate alternative of market development of Feathers based on Noomor 9 Year 2013 Regulation on Traditional Market Setting. The research method used in this research is descriptive qualitative method. The theory used is the theory of brigman and Davis which mentions there are five stages of policy analysis are among others (1) Formulate policy formulation; (2) Determining Policy Objectives (3) Identifying Policy Parameters; (4) finding policy alternatives; (5) Decide on alternative policy. The parameters in this policy analysis use parameters from Patton and Sawicky which state there are four criteria in assessing policy alternatives: technical feasibility, economic and financial possibilities, political feasibility and administrative feasibility. The results of the research indicate that the policy alternatives found in the implementation of the Bulu market development policy are (1) to improve the market management of Feathers covering the availability and maintenance of market facilities, the arrangement of market zoning, the availability of market security and the empowerment of market traders; (2) Increasing compliance of market traders Furs (3) increasing acceptance of market levies Feathers (4) enhancing market competitiveness Feathers. The chosen alternative is to improve the market management of Feathers by stating that the research findings of the researcher is an elite model in the policy-making model